Taxonomic identity of Theriophonum danielii and T. manickamii (Araceae) (Bangladesh Journal of Plant Taxonomy, 2014)
The genus Theriophonum (Araceae), represented by seasonally dormant tuberous perennials is endemic to India and Sri Lanka. Critical taxonomic appraisal of the constituent species supports existence of only five species, viz. T. dalzellii, T. fischeri, T. infaustum, T. minutum and T. sivaganganum, and all are with restricted distribution in India. Theriophonum minutum is the only species with extended distribution in Sri Lanka. The recently described T. danielii and T. manickamii are considered here as conspecific with T. infaustum and T. fischeri, respectively.DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19269Bangladesh J. Plant Taxon. 21(1): 63-70, 2014 (June)